Super-enhancer-driven long non-coding RNA LINC01503, regulated by TP63, is over-expressed and oncogenic in squamous cell carcinoma - Xie, Jian-Jun (2019)
Background & Aims: Long non-coding RNAs (lncRNAs) are expressed in tissue-specific pattern, but it is not clear how these are regulated. We aimed to identify squamous cell carcinoma (SCC)-specific lncRNAs and investigate mechanisms that control their expression and function. Methods: We studied expression patterns and functions of 4 SCC-specific lncRNAs. We obtained 113 esophageal SCC (ESCC) and matched non-tumor esophageal tissues from a hospital in Shantou City, China, and performed quantitative reverse transcription polymerase chain reaction assays to measure expression levels of LINC01503. We collected clinical data from patients and compared expression levels with survival times. LINC01503 was knocked down using small interfering RNAs and oligonucleotides in TE7, TE5, and KYSE510 cell lines and overexpressed in KYSE30 cells. Cells were analyzed by chromatin immunoprecipitation sequencing, luciferase reporter assays, colony formation, migration and invasion, and mass spectrometry analyses. Cells were injected into nude mice and growth of xenograft tumors was measured. LINC01503 interaction with proteins was studied using fluorescence in situ hybridization, RNA pulldown, and RNA immunoprecipitation analyses. Results: We identified a lncRNA, LINC01503, which is regulated by a super enhancer and is expressed at significantly higher levels in esophageal and head and neck SCCs than in non-tumor tissues. High levels in SCCs correlated with shorter survival times of patients. The transcription factor TP63 bound to the super enhancer at the LINC01503 locus and activated its transcription. Expression of LINC01503 in ESCC cell lines increased their proliferation, colony formation, migration, and invasion. Knockdown of LINC01503 in SCC cells reduced their proliferation, colony formation, migration, and invasion, and the growth of xenograft tumors in nude mice. Expression of LINC01503 in ESCC cell lines reduced ERK2 dephosphorylation by DUSP6, leading to activation of ERK signaling via MAPK. LINC01503 disrupted the interaction between EBP1 and the p85 subunit of PI3K, increasing AKT signaling. Conclusions: We identified an lncRNA, LINC01503, which is increased in SCC cells compared with non-tumor cells. Increased expression of LINC01503 promotes ESCC cell proliferation, migration, invasion, and growth of xenograft tumors. It might be developed as a biomarker of aggressive SCCs in patients.